Old World Conventions and New World Curiosities: North American Landscapes Through European Eyes - Dewar, Helen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2003)
AbstractThis paper examines the published accounts of three British travellers, Patrick Campbell (fl. c. 1765-1823), Isaac Weld (1774-1856), and George Heriot (1759-1839), to North America in the late eighteenth century. Focusing specifically on the travellers' scientific approaches to the natural landscape, it argues that they drew on eighteenth-century European scientific developments, including empirical observation, the evolution and instability of matter, and systems of classification, to facilitate their understanding of unfamiliar phenomena. The travellers' scientific observations revealed both an intellectual interest in the origin of landforms and a utilitarian view of wildlife and natural resources. Attracted to the novel and curious, the travellers' scientific speculations merged with initial aesthetic responses, highlighting a preoccupation with the power, spontaneity and magnitude of nature.